2020
DOI: 10.3390/jpm10030119
|View full text |Cite
|
Sign up to set email alerts
|

Application of Noninvasive Vagal Nerve Stimulation to Stress-Related Psychiatric Disorders

Abstract: Background: Vagal Nerve Stimulation (VNS) has been shown to be efficacious for the treatment of depression, but to date, VNS devices have required surgical implantation, which has limited widespread implementation. Methods: New noninvasive VNS (nVNS) devices have been developed which allow external stimulation of the vagus nerve, and their effects on physiology in patients with stress-related psychiatric disorders can be measured with brain imaging, blood biomarkers, and wearable sensing devices. Advantages in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 297 publications
(327 reference statements)
0
28
0
Order By: Relevance
“…Studies in both animals and humans showed that catecholamines released during stress act through the adrenergic receptor to activate the transcription factor, nuclear factor-κB (NF-κB), which leads to increases in cytokines, including IL-6 ( Bierhaus et al, 2003 ). Intervention at the level of IL-6 with VNS may be a useful intervention that reduces symptoms by targeting the underlying neurobiology of PTSD( Bremner et al, 2020b ; Noble et al, 2019 ; Souza et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies in both animals and humans showed that catecholamines released during stress act through the adrenergic receptor to activate the transcription factor, nuclear factor-κB (NF-κB), which leads to increases in cytokines, including IL-6 ( Bierhaus et al, 2003 ). Intervention at the level of IL-6 with VNS may be a useful intervention that reduces symptoms by targeting the underlying neurobiology of PTSD( Bremner et al, 2020b ; Noble et al, 2019 ; Souza et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Neuromodulation is a new approach that may be particularly useful in addressing the underlying psychobiology of stress-related psychiatric disorders ( Adair et al, 2020 ; Bikson et al, 2016 ; Bikson et al, 2017b ; Bremner et al, 2020b ; Krames et al, 2018 ; Schachter and Saper, 1998 ; Tortella et al, 2015 ; Woods et al, 2016 ). Vagal Nerve Stimulation (VNS) is a form of neuromodulation that has been shown to be efficacious in the treatment of epilepsy ( Ben-Menachem et al, 1999 ; Ben-Menachem et al, 1994 ; George et al, 1994 ; Handforth et al, 1998 ; Salinsky et al, 1999 ; The Vagus Nerve Stimulation Study Group, 1995 ) and treatment-refractory major depression ( Aaronson et al, 2017 ; Berry et al, 2013 ; Dell-Osso et al, 2013 ; George et al, 2005 ; George et al, 2003 ; George et al, 2000 ; Marangell et al, 2002 ; Rush et al, 2000 ; Rush et al, 2005a ; Rush et al, 2005b ; Sackeim et al, 2007 ; Sackeim et al, 2001a ; Sackeim et al, 2001b ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing duration of stress is expected to result in a shift from potentially adaptive changes to potentially detrimental changes, initially in cellular immunity and then in immune function more broadly 29 . Vagus Nerve Stimulation has been found to have a direct effect in managing stress and diseases born out of it 30 . Pranayama practices have been found to have a direct impact on Vagus Nerve stimulation 31 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Another possible application could be evaluation of targeted neuromodulation; specifically, there is clinical interest in stimulating the vagus nerve, which is involved with responses in cardiovascular, pulmonary, gastrointestinal, renal, hepatic, and endocrine systems (Chavan et al, 2017; Pavlov et al, 2018). Vagus nerve stimulation (VNS) has been used in previous studies for multiple conditions, including refractory epilepsy (Stefan et al, 2012; Rong et al, 2014), depression (Rong et al, 2016; Kong et al, 2018), PTSD (Bremner et al, 2020), pre-diabetes (Huang et al, 2014), tinnitus (Shim et al, 2015), stroke (Redgrave et al, 2018), and others, including oromotor dysfunction, rheumatoid arthritis, and obesity (Guiraud, et al, 2016). These studies have used a range of electrical stimulation settings and sites, and there is no optimal dose or set of parameters (Badran et al, 2018); the mechanism of VNS and responses are not well understood.…”
Section: Discussionmentioning
confidence: 99%